Recuperación de residuos líquidos en la industria de impresión flexográfica (2018)
The graphic printing industry in Colombia is growing as the generation of hazardous waste associated with printing operations. Most of these are not used, so, they generate additional costs when third parties are required to handle, treat and dispose them. In other cases, they are not adequately disposed generating pollution. It is essential to propose processes that are able to recovery the compounds of these residues to prevent environmental impacts generated by them. At the same time, obtain products that can be reused in the printing ink sector or other value-added products. In a first stage, the recovery of the solvents has been considerate since they represent about 93 % of the total waste mixture, by a simple distillation process were obtained a recovery of approximately 95 % of the solvents in the waste mixture. However, the residue remain has not been used yet. So in the research group of unconventional separation processes of the University of America is doing an investigation that allows the recovery of pigments. Since they have the greater economic cost and their disposition in security cells is expensive, this article focuses on the study of the background of printing industry, its waste and antecedents about technologies used for the treatment of waste ink or samplings chemically similar.